Egressos do curso de licenciatura em educação física (2003-2010) : mapeamento inaugural das suas trajetórias - Reis, Merielle Soares de Araujo (2013)
This study comprises a larger research that aims to track students who graduated from Physical Education, Federal University of Espírito Santo, in order to analyze and understand their profile and route / professional career since his departure from the university. Given the pioneering nature of this task and the fact that our dissertation occupies a very specific in this extensive project, with responsibility to inaugurate it, we had to take several decisions to reach our object and our goals. Thus, our study consisted in locating UFES Physical Education graduates degree formed between the 1st period of 2003 and 2nd period 2010 to trace career and professional training aspects. By this, we had a double purpose: first, we have built a database about these graduates, and secondly, diagnose and systematize a set of problems, clippings, questions and explanatory hypotheses that these data showed. As a methodological approach, we opted for quantitative and qualitative research and justify thus use the model survey research. Therefore divided between description and explanation. Data were collected through a questionnaire applied to all graduates located (95.73%) and allowed the design of the profile of the studied group. They replied our questionnaire (34.87%) that means 188 graduates. It was possible to inventory issues quite significant from a preliminary analysis of the data presented in tables and the charts, such as: a) the issue of gender in professional activities in Physical Education, b) the search for stability in employment in contradiction with the happy to work in teaching profession c) conflicts between initial training and performance in schools, d) graduate with no greater meaning for professional development. Every effort devoted to this study leads us to understand that we are in an initial process, which has been checked several points needing further attention and work, given the scope of the topic. Thus, we are sure that this dissertation will help future researchers in their studies contributing to the improvement of the UFES Physical Education Course.